Cell penetrating peptide: A potent delivery system in vaccine development - Behnam Hasannejad-Asl; Behnam Hasannejad-Asl; Farkhondeh Pooresmaeil; Farkhondeh Pooresmaeil; Shahla Takamoli; Mehran Dabiri; Azam Bolhassani (Frontiers Media S.A., 2022)
One of the main obstacles to most medication administrations (such as the vaccine constructs) is the cellular membrane's inadequate permeability, which reduces their efficiency. Cell-penetrating peptides (CPPs) or protein transduction domains (PTDs) are well-known as potent biological nanocarriers to overcome this natural barrier, and to deliver membrane-impermeable substances into cells. The physicochemical properties of CPPs, the attached cargo, concentration, and cell type substantially influence the internalization mechanism. Although the exact mechanism of cellular uptake and the following processing of CPPs are still uncertain; but however, they can facilitate intracellular transfer through both endocytic and non-endocytic pathways. Improved endosomal escape efficiency, selective cell targeting, and improved uptake, processing, and presentation of antigen by antigen-presenting cells (APCs) have been reported by CPPs. Different in vitro and in vivo investigations using CPP conjugates show their potential as therapeutic agents in various medical areas such as infectious and non-infectious disorders. Effective treatments for a variety of diseases may be provided by vaccines that can cooperatively stimulate T cell-mediated immunity (T helper cell activity or cytotoxic T cell function), and immunologic memory. Delivery of antigen epitopes to APCs, and generation of a potent immune response is essential for an efficacious vaccine that can be facilitated by CPPs. The current review describes the delivery of numerous vaccine components by various CPPs and their immunostimulatory properties.